Maritime communication: From flags to the VHF Data Exchange System (VDES). (2nd July 2020) - Golaya, Arun Pratap; Yogeswaran, Nithiyanandam
ABSTRACT: Very high frequency (VHF) communication has been extensively used for maritime applications including, in the recent past, space-based communication and vessel tracking. In 2015, the International Telecommunication Union (ITU) published the "Technical Characteristics for a VHF Data Exchange System in the VHF Maritime Mobile Band". The proposed system, which is a work in progress, envisages a composite VHF Data Exchange System (VDES) that will integrate the functions of existing messaging and ship-tracking/anti-collision systems. The system shall thereby enable tracking of ships as well as transfer of messages between ships and from ship to shore. Satellite uplink and downlink components are also integral to the system. This paper briefly traces the history of maritime communication since the Battle of Trafalgar and examines how communication is evolving in the digital age. This VDES "primer" focuses on the envisaged uses of the system, rather than technical characteristics or the architecture itself.